Controlling the network type in self-assembled dipeptide hydrogels. Issue 9 (10th February 2017) - Colquhoun, Catherine; Draper, Emily R.; Schweins, Ralf; Marcello, Marco; Vadukul, Devkee; Serpell, Louise C.; Adams, Dave J.
Abstract : The mechanical properties of low molecular weight hydrogels can be varied by altering the method by which gels are formed. Abstract : We show that the same low molecular weight gelator can form gels using three different methods. Gels were formed from a high pH solution either by adding a salt or by adding an acid; gels were also formed by adding water to a solution of the gelator in an organic solvent. The mechanical properties for the gels formed by the different methods are different from one another. We link this to the network type that is formed, as well as the fibrous structures that are formed. The salt-triggered gels show a significant number of fibres that tend to align. The acid-triggered gels contain many thin fibres, which form an entangled network. The solvent-triggered gels show the presence of spherulitic domains. We show that it is tractable to vary the trigger mechanism for an established, robust gelator to prepare gels with targeted properties as opposed to synthesising new gelators.